Про роль атомів бору в формуванні електронної структури аморфних сплавів на основі заліза - Плющай, І.В.; Захаренко, М.І.; Макара, В.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The role of boron atoms in the formation of the electronic structure of Fe–B-based amorphous metallic alloys (AMA) has been analyzed. In particular, the problem of the boron charge state has been considered. The energy dependence of the density of electronic states has been calculated for the model systems corresponding to the amorphous Fe and AMA Fe80B20 using the LMTO method. The main contribution to the density of electronic states in the vicinity of the Fermi level is shown to be determined by 3d-electrons of iron. The doping with boron leads to the splitting of the 3d-peak into bound and antibound subbands, which places the Fermi level within the pseudogap between these subbands. This reduces the density of electronic states at the Fermi level that is in agreement with the Nagel-Tauc criterion of the amorphous state stability. The performed calculation and the experimental X-ray emission spectra prove that boron atoms are the electron acceptors in the Fe-based AMAs.